PERCEIVED PRODUCT QUALITY AND BRAND EXPERIENCE ON PURCHASE DECISION: THE MEDIATING ROLE OF BRAND IMAGE AT ERIKA EXOTICBAG - Jovanka Fauzia Mantiri; I Wayan Santika; Anak Agung Gede Agung Artha Kusuma; Komang Agus Satria Pramudana (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study investigated the influence of perceived product quality and brand experience on purchase decisions, with brand image treated as a mediating variable, among consumers of Erika Exoticbag, an Indonesian premium fashion label built on exotic reptile leather. A total of 150 respondents who had purchased or were otherwise familiar with the brand were recruited through purposive sampling. Data will be collected using a five point Likert scale questionnaire and processed with Partial Least Square Structural Equation Modeling (PLS SEM) through SmartPLS. The measurement model confirmed that every indicator met the required standards of validity and reliability. The structural model further showed that perceived product quality and brand experience each produced a positive and significant effect on both purchase decisions and brand image. Brand image itself also exerted a positive and significant effect on purchase decisions and functioned as a complementary partial mediator linking the two exogenous variables to purchase decisions. These results reinforce the relevance of the Stimulus Organism Response framework for explaining purchasing behavior toward niche, exotic fashion products. From a managerial standpoint, the findings underline the importance of strengthening product durability and cultivating brand experiences that encourage repeat purchases, both of which are essential for the continued growth of Erika Exoticbag.